New 3he Neutron Monitor for Chilean Cosmic-Ray Observatories from the Altiplanic Zone to the Antarctic Zone - Salazar-Aravena, D (2012)
We present the results of three years of continuous operations and the principal characteristics of our new 3He neutron monitors installed in the Chilean Network of Cosmic-Ray Observatories. During the years 2004 and 2005, we began the construction of this International Geophysical Year (IGY)-type 3He neutron monitor, with the intention of replacing the older proportional tubes of the BF 3. These new monitors are installed in stations at locations ranging from the near-equatorial zone to the Antarctic zone. As a reference system, we used our own BF 3 neutron monitors and previously complemented the collected data with a Monte Carlo simulation for the proton-yield function response of the Putre neutron monitor. Herein, we present for the first time the data obtained from our new high-mountain observatory located in the Altiplanic zone. © 2012 COSPAR. Published by Elsevier Ltd. All rights reserved.